When the Stakes are Low: How Key Features of Momentary Suspense Contribute to a Global Evaluation of Enjoyment. (April 2023) - Madrigal, Robert; Bee, Colleen; Chen, Johnny
The enjoyment of suspenseful competitions is thought to be motivated by outcome preferences and outcome uncertainty. Prior research has focused more on the former than the latter. The current research considers how outcome uncertainty predicts a global evaluation of enjoyment for competitions in which the personal stakes associated with the outcome are relatively low. Using moment-to-moment (MTM) measures of suspense, we find that competitions with more (vs. less) outcome uncertainty positively predict both total suspense and a set of key features aggregated from MTM suspense (slope, end, peak, and time-to-peak). A global evaluation of enjoyment was also predicted by these same measures. Further, enjoyment in each experiment was more highly correlated with peak suspense than it was with total suspense. Our contribution therefore is a nuanced description of how certain key features of suspenseful competitions with low-stakes outcomes influence a global evaluation of enjoyment.